The Idea of a Post Colonial University - Rhody-Ann Thorpe (PRISM)
Universities in the English-speaking world may trace their origins to England, where the first universities of Oxford and Cambridge were established. These universities were, for centuries, the models for universities to come both in terms of structure and philosophy; and they also became a tool of British colonial policy. With the progression of British expansionism, many English men penned their ideas of a university; some of which were brought to fruition. In the 21st century, we have a multiplicity of independent nations which were formerly under British rule. While in most societies there was a phasing out of colonial institutions, many universities established during the colonial epoch seem to have withstood the test of time. It would be interesting therefore to assess some of these institutions and their evolutions in a broader endeavour to examine developments in higher education in societies post-independence. What conversations were had prior to independence regarding higher education? What ideas of a post-colonial university prevailed and what ideas should have been put forth? Were there shifts away from what constituted a colonial university? This paper is also an attempt to include universities in the post-colonial discourse and to propose an ideals of the university from a post-colonial perspective.